Conformationally rigid pyrazoloquinazoline α-amino acids: one- and two-photon induced fluorescence. Issue 12 (20th January 2020) - Bell, Jonathan D.; Harkiss, Alexander H.; Nobis, David; Malcolm, Eilidh; Knuhtsen, Astrid; Wellaway, Christopher R.; Jamieson, Andrew G.; Magennis, Steven W.; Sutherland, Andrew
Abstract : Conformationally rigid unnatural α-amino acids bearing a pyrazoloquinazoline ring system that are amenable to both one- and two-photon excitation have been developed as new fluorescent probes. Abstract : The synthesis and photophysical properties of a new class of α-amino acid bearing a rigid pyrazoloquinazoline chromophore are described. Confromational constraint of the amino acid side-chains resulted in high emission quantum yields, while the demonstration of two-photon-induced fluorescence via near-IR excitation signifies their potential for sensitive bioimaging applications.